2017
DOI: 10.1177/0009922816684600
|View full text |Cite
|
Sign up to set email alerts
|

Screen Exposure During Daily Routines and a Young Child’s Risk for Having Social-Emotional Delay

Abstract: This cross-sectional study assessed associations between social-emotional development in young children and their number of daily routines involving an electronic screen. We hypothesized children with poor social-emotional development have a significant portion of daily routines occurring with a screen. Two hundred and ten female caregivers of typically developing children 12 to 36 months old completed the Ages and Stages Questionnaire: Social-Emotional (ASQ: SE) and a media diary. Caregivers completed the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…Screen time was negatively associated with behavioral and emotional outcomes in 14 studies. Children with excessive screen time were related to social-emotional delay [ 100 , 106 ], hyperactivity-inattention [ 100 , 101 , 105 , 107 , 108 ], emotional symptoms [ 99 , 101 , 102 , 103 ], prosocial behavior [ 99 , 101 , 102 , 103 ], peer problems [ 99 , 101 , 102 , 103 ], and conduct problems [ 99 , 101 , 102 , 103 ]. The positive association between screen time and bullying including being a victim or being a bully was reported by three studies [ 23 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Screen time was negatively associated with behavioral and emotional outcomes in 14 studies. Children with excessive screen time were related to social-emotional delay [ 100 , 106 ], hyperactivity-inattention [ 100 , 101 , 105 , 107 , 108 ], emotional symptoms [ 99 , 101 , 102 , 103 ], prosocial behavior [ 99 , 101 , 102 , 103 ], peer problems [ 99 , 101 , 102 , 103 ], and conduct problems [ 99 , 101 , 102 , 103 ]. The positive association between screen time and bullying including being a victim or being a bully was reported by three studies [ 23 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, LSAC only assessed duration of media exposure, not other aspects of media use linked with child development, such as content quality, 14,27,29 use of media to calm child distress, 9 or use at meals or bedtime. 30 This study also used a composite measure of selfregulation, while other studies have examined constructs such as social-emotional development (including emotion regulation) 9,30 or executive functioning (including cognitive regulation). 14,29 Our results indicated that associations between self-regulation at 4 years and total media exposure, computer use, and electronic game use at 6 years were stronger among children of tertiary educated rather than high school educated caregivers.…”
mentioning
confidence: 99%
“…Evidence from the included articles, combined with knowledge of the Scandinavian model of preventive care, highlights many opportunities. First steps include norming the latest versions of the ASQ and ASQ:SE and then evaluating their impact in home‐visit, primary care medical, and early learning/preschool settings.…”
Section: Discussionmentioning
confidence: 99%